PENGARUH PIJAT BAYI TERHADAP PENINGKATAN BERAT BADAN BAYI DENGAN RIWAYAT BBLR - Sriwahyuni, Eka; Sari, Nurmala; Nainggolan, Aurina (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
According to World Health Organization guidelines, low birth weight (LBW) refers to a birth weight of less than 2500 grams. It is one of the leading causes of infant mortality in Indonesia and globally. Baby massage is one method that may be used to help a baby gain weight if they have a history of LBW. The purpose of the study is to examine the impact of infant massage at the DIANA District KUALA clinic on the rise in baby weight in those with a history of BBLR who are between the ages of three and four months. Pre-experimental in nature, this kind of study uses a single grub prestest-posttest design. The sample approach employed in this study is complete sampling, and the group includes infants with a history of LBW as young as 3–4 months old and up to 8 newborns. This study instrument uses questionnaires, with the dependent variable being the infant's weight reduction with a history of low birth weight (LBW) at ages three to four months and the independent variable being baby massage. Editing, coding, tabulating, and Wilcoxon statistical tests are all used in data management. The findings of this study demonstrated that the improvement of a baby's body with a history of LBW age 3–4 months after receiving a massage all good, that is, 8 people (100%) and the increase in baby weight with a history of LBW age 3–4 months who has not received a baby massage as a large is not good. Ha was approved based on the results of the Wilcoxon statistical tests, which revealed a significant value of p value = 0.001 < α (0.05). The study's findings indicates that infant massage may have an impact on a baby's rise in weight if the baby has a history of low birth weight (LBW) in KLINIK Bidan Neri Kec. Sunggal Kab. Deli Serdang Tahun 2023.